Lilith entre a profanação e a paródia: uma leitura de Caim de Saramago - Silva, Iane Christina Alves Rodrigues da (2021)
The author José Saramago presents, in his works, questions about the parameters imposed by a religious system that he considered contradictory, considering that many barbarities were committed in the name of God. The author uses literary tools such as parody to deconstruct the sacred scriptures, causing us to reflect on: the position of women in the social context, the discussion on the position of the marginalized in society and the various faces of God postulated by the Old Testament. All these themes will serve as raw material for the study of parody and desecration in the work Caim (2009). The focus is on the profane transfigurations of the Jewish mythical figure Lilith, present in the work. In this fiction, we find traces of the medieval parody theorized by Mikhail Bakhtin (1987), and also of the modern one, argued by Linda Hutcheon (1985) and Affonso Romano de Sant’Anna (1988). Based on the theories of Mircea Eliade (2001), Giorgio Agamben (2007) and Paul Ricoeur (2013), we will develop the analysis regarding the way the profane is linked to the text so that some religious questions are evidenced. Lilith is a figure traditionally known to carry a negative aspect due to her unsubmitted character, however, some concepts about her, free from the dogmas of religion, will be re-signified by Saramago in Cain.